MANAJEMEN PENDIDIKAN ISLAM DALAM PENGAJARAN BAHASA ARAB: STRATEGI DAN IMPLEMENTASI UNTUK PENINGKATAN KUALITAS PEMBELAJARAN - Satrio (As-Sulthan Journal of Education, 2024)
This study aims to analyze the issues in Arabic language teaching in Islamic educational institutions and find solutions within the context of Islamic education management. Although Arabic plays a crucial role in understanding Islamic teachings, its teaching faces several challenges, such as low student interest, limited learning resources, and the lack of integration of Arabic in daily life. This study employs a qualitative approach with a literature review method to identify the hindering factors and strategies for managing Arabic language teaching. The findings indicate that integrating learning technology, continuous teacher training, and implementing practice-based teaching methods can enhance the quality of Arabic teaching. In conclusion, innovative Islamic education management can address the challenges in Arabic language teaching and lead to more effective, relevant, and engaging learning experiences for students.